Social Vulnerability Measurement Tool - Rahmanto Kusendi; Baydhowi; Nangoi Priscilla Francis; Albertus Galih Prawata (Talenta Publisher, 2026)
The construct of the Social Vulnerability measuring instrument aims to measure the domain of social weakness or threats in an area. The danger of vulnerability measured is related to three leading indicators, social identity causing social marginality, economic problems caused by extreme events, and monetary property conditions. The SV measuring instrument consists of 11 statement items (SOV11) divided into three sub-dimensions, namely Demographic Characteristics (DC) three statements, Socio-Economic Status (SES) five view and Public Resources Provision (PRP) three opinions with a total measuring instrument is eleven points positive statement. Based on trials on 94 residents of the Koja area, North Jakarta, the reliability coefficient value was 0.848. From the results obtained, this social vulnerability measurement tool (SOV11) can be used to examine the population living in urban coastal areas, especially the city of North Jakarta. This measuring tool was developed from the social vulnerability theory of Fatemi, Ardalan, Aguirre, Mansouri, & Mohammadfam [13].